NOTIFICATION !!! - Conference Papers (European Scientific Journal, ESJ, 2015)
The content of this ESJ special edition is an outcome of the conference “International Conference on tourism vs heritage” which was held in February 2015 in Lisbon, Portugal. The papers have been reviewed by the conference committee.